DNA induced aggregation of stem bromelain; a mechanistic insight. Issue 44 (15th April 2016) - Zaman, Masihuz; Chaturvedi, Sumit Kumar; Zaidi, Nida; Qadeer, Atiyatul; Chandel, Tajalli Ilm; Nusrat, Saima; Alam, Parvez; Khan, Rizwan Hasan
Abstract : Negatively charged species such as nucleic acids have commonly been found to be associated with the proteinaceous deposits in the tissues of patients with amyloid diseases. Abstract : Negatively charged species such as nucleic acids have commonly been found to be associated with the proteinaceous deposits in the tissues of patients with amyloid diseases. Numerous studies have demonstrated that various environmental and intracellular factors affect the fibrillation property of proteins, by accelerating the process of assembly. Thus in the present study, the effect of calf thymus DNA (CT-DNA) on stem bromelain, a proteolytic phytoprotein, is investigated at pH 2.0, using multiple approaches that include turbidity measurements, Rayleigh light scattering, dye binding assay (ThT and ANS), far-UV circular dichroism, dynamic light scattering fluorescence microscopy and transmission electron microscopy. Large sized β-sheet aggregates of SB are found in the presence of CT-DNA at pH 2.0. The propensity for aggregation concomitantly increases with increasing concentration of CT-DNA (0–100 μM) and levels off at higher concentration of CT-DNA (beyond 100 μM). Isothermal titration calorimetric results confirmed that an electrostatic interaction between positively charged SB at pH 2.0 and the negatively charged phosphate group of CT-DNA is the probable mechanism behind aggregate formation. However, the hydrophobic interaction between CT-DNA and SB cannot be neglected. The survival of aggregates even after treatment with DNase indicates that intact CT-DNA is not necessarily required for SB aggregation.